2019
DOI: 10.1038/s41598-019-54880-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3T and 7T MRI for the visualization of globus pallidus sub-segments

Abstract: The success of deep brain stimulation (DBS) targeting the internal globus pallidus (GPi) depends on the accuracy of electrode localization inside the GPi. In this study, we sought to compare visualization of the medial medullary lamina (MML) and accessory medullary lamina (AML) between proton density-weighted (PDW) and T2-weighted (T2W) sequences on 3T and 7T MRI scanners. Eleven healthy participants (five men and six women; age, 19–28 years; mean, 21.5) and one 61-year-old man were scanned using two-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Finally, ultra-high-field imaging with 7T MRI has become increasingly popular due to its higher signal-to-noise ratio, spatial resolution, and structural contrast compared to 1.5T or 3T scanners ( 72 ). Ultra-high-field imaging may improve the visualization of the STN ( 73 ), the GPi ( 74 ), and thalamic nuclei ( Figure 3 ) ( 58 , 76 ). Currently, 7T MRI scanners are limited in availability to specialized imaging centers; however, as access to these scanners increases, more routine use in neurosurgical planning will become more common.…”
Section: Dbs Targeting Strategiesmentioning
confidence: 99%
“…Finally, ultra-high-field imaging with 7T MRI has become increasingly popular due to its higher signal-to-noise ratio, spatial resolution, and structural contrast compared to 1.5T or 3T scanners ( 72 ). Ultra-high-field imaging may improve the visualization of the STN ( 73 ), the GPi ( 74 ), and thalamic nuclei ( Figure 3 ) ( 58 , 76 ). Currently, 7T MRI scanners are limited in availability to specialized imaging centers; however, as access to these scanners increases, more routine use in neurosurgical planning will become more common.…”
Section: Dbs Targeting Strategiesmentioning
confidence: 99%
“…There are strong incentives to do so: increasing the strength of the static magnetic field substantially increases the signal-to-noise ratio to visualize small structures previously unobservable on MRI scans. For example, MRI at 7 T can differentiate subsegments of the globus pallidus, a small brain nucleus that is the target of neuromodulation therapies, such as deep brain stimulation (DBS) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Steensma et al, eg, showed that for imaging the prostate a higher SNR could be achieved using 7 T 32 . Similarly, Maruyama et al described a superior delineation of anatomical brain structures on 7 T, while Harteveld et al showed that small lesions in the arterial vessel walls could be visualized much better on 7 T than on 3 T 33,34 . However, unlike the aforementioned studies with up to 20 minutes per sequence, imaging the eye requires short acquisition times to limit eye‐motion related artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased signal intensity at 7 T, a better delineation at 7 T could be expected, as this was also observed in different studies of other anatomies. Steensma et al, eg, showed that for imaging the prostate a higher SNR could be achieved using 7 T. 32 Similarly, Maruyama et al described a superior delineation of anatomical brain structures on 7 T, while Harteveld et al showed that small lesions in the arterial vessel walls could be visualized much better on 7 T than on 3 T. 33 , 34 However, unlike the aforementioned studies with up to 20 minutes per sequence, imaging the eye requires short acquisition times to limit eye‐motion related artifacts. As a result, the image resolution was limited by the number of k‐space lines that could be acquired within 4 minutes.…”
Section: Discussionmentioning
confidence: 99%